Operational Risk Management in A Commercial Bank - I.Vasiliev, I.; A. Smelov, P.; V. Klimovskih, N.; G. Shevashkevich, M.; N. Donskaya, E. (International Journal of Engineering and Technology, 2018)
The existing financial and economic situation in the world and in Russia impacts the activities of all sectors of the economy, including posing challenges for banks. In the conditions of prolonged instability, the banking community has to pay great attention to the risks taken and to manage them. Among all the risks that the bank is exposed to, operational risks represent a separate group due to its specifics, a lack of a systematic approach to analysis and a lack of identification criteria requiring more detailed study. The operational risk is unique in that, although it affects virtually all areas of the credit institution, it is difficult to establish and separate it from other bank risks. It should be noted that every year there appear all new types of operational risk that have a strong impact on the activities of the credit institution due to the development of information and computer systems, the complication of the instruments of the stock market and the improvement of business methods. Therefore, regulators of all countries try to constantly improve the regulatory framework related to the management of the operational risk of a commercial bank, based on the recommendations given by the Basel Committee on Banking Supervision.The article is aimed at developing an effective system for managing the operational risk of a commercial bank.The empirical level research methods used in this article are a description of what operational risk is, its types, tools and methods of assessment; comparison of operational risk management systems in the studied banks; generalization, analysis and synthesis of the information received; the hypothetical-deductive method is used at the theoretical level.Modernization and improvement of the operational risk management system helps stabilize the bank, increase stability and increase profitability, reduce the provision of capital for operational risk, and increase the attractiveness of banking services for consumers, thus benefiting a credit institution among competitors. In today's financial environment, the effective operational risk management is inherent in the long-term development strategy.Â